Manual for Scaling Community-Based Breeding Programs for Sheep and Goats - Ministry of Agriculture, Ethiopia (Ministry of Agriculture, Ethiopia, 2024)
The Community-Based Breeding Program (CBBP) for sheep and goats in Ethiopia has proven to be a successful genetic improvement project since its establishment in 2009. This program effectively involves local communities in various aspects, such as identifying and collecting data on animals, managing and using breeding sires, utilizing traditional knowledge, and mobilizing community flocks to enhance their sheep and goat stock. It achieves this by engaging community members in participatory selection processes based on the estimated breeding value of the animals while also considering the specific needs of the community. The manual consists of two parts: Implementing a Scaling Framework for a Specific Breed of Animals and Procedure for Implementation.